SISTEM INFORMASI MANAJEMEN SUMBER DAYA MANUSIA BERBASIS WEB (STUDI KASUS: PT. KLIK TEKNOLOGI INDONESIA) - Nia Kusuma Wardhani; Muhammad Thariq Abdul Aziz (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2018)
The need for technology to handle various problems quickly and precisely is growing, especially for human resource management (HRM) information systems. The activity of manually recording employee data is very time-consuming and effortless so it is inefficient and results in a high percentage of data errors. With information technology, it is expected that company data, especially employee data, can be processed quickly and the data presented will be neater, so the percentage of errors is also reduced. The object of this research is PT. Klik Teknologi Indonesia, where HRM in this company has not been supported by information system technology. Management of leave and reimburse is still managed manually. Another problem that occurs is about the attendance of employees who work remotely, where there is no system to handle it, making it difficult to manage attendance data from these employees. This is the basis of research and development of web-based HRM information systems created with the Unified Modeling Language (UML) method using waterfall model, while the programming language used is Ruby, with Ruby on Rails framework and PostgreSQL database. From the implementation of the system it can be concluded that the HRM information system makes the management of human resources in the company easier, faster and more accurate, besides the system created provide facilities to perform virtual absences in real time, so that data can be managed by HR department.